Preparation of B4C–ZrB2–SiC ternary eutectic composites by arc melting and their properties. (December 2015) - Tu, R.; Li, N.; Li, Q. Z.; Zhang, S.; Goto, T.; Zhang, L. M.
Abstract : B4 C–ZrB2 –SiC composites were synthesised by arc melting in Ar atmosphere using B4 C, ZrB2 and β -SiC powders as starting materials. The ternary eutectic composition of 40B4 C–20ZrB2 –40SiC (mol-%) was first identified and a lamellar eutectic texture was observed. SiC and ZrB2 grains about 1 μm in thickness were uniformly dispersed in B4 C matrix of B4 C–ZrB2 –SiC eutectic composite. B4 C (003) and ZrB2 (100) planes were perpendicular to the growth direction. The Vickers hardness of B4 C–ZrB2 –SiC ternary eutectic composite was 30–34 GPa. The fracture toughness of B4 C–ZrB2 –SiC composite increased with the decrease of B4 C content and the rise of ZrB2 content.